A study on histopathological changes in lesions of vitiligo in Karnataka population - Nagaral, Girish V.; ., Karibasappa (International Journal of Research in Dermatology, 2017)
Background: Vitiligo is considered to be symptom less and its presentation is boundless varying from isolated focal lesion to bizarre generalized lesions. The present study was undertaken to study the histopathological changes in lesions of vitiligo in south Indian population. Methods: 150 patients with mild to moderate vitiligo features attending the outpatient department of Dermatology, Venereology and Leprology at Chitageri General Hospital and Bapuji Hospital attached to J.J.M Medical College, Davengere were utilized to study the histopathological features in vitiligo and its association with other diseases. Results: Destruction of melanocytes at dermo-epidermal junction was noted. We have observed presence of melanocytes in the basal layer of the epidermis on left side of the lesion, whereas decreased melanocytes in the basal layer of the epidermis on the right side of the same lesion in the present study. Dermis with mild perivascular lymphocytic infiltration and acanthosis along with mono nuclear cell infiltration in the upper dermis was observed. Conclusions: The present study gives better knowledge to the clinicians about the lesions of vitiligo and its pathogenesis.